2018
DOI: 10.1007/s11920-018-0972-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens, Aging, and Working Memory

Abstract: Purpose of ReviewWorking memory (WM) is a key process that is integral to many complex cognitive tasks, and it declines significantly with advancing age. This review will survey recent evidence supporting the idea that the functioning of the WM system in women is modulated by circulating estrogens.Recent FindingsIn postmenopausal women, increased estrogen concentrations may be associated with improved WM function, which is evident on WM tasks that have a high cognitive load or significant manipulation demands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 81 publications
1
25
1
Order By: Relevance
“… 18 , 19 The regulation of cognitive function by estrogen is usually associated with the activation of the prefrontal cortex, which regulates the activation of cognition-related regions in the cerebral cortex. 20 , 21 In this study, we found that the ALFF value of the left gyrus rectus was increased, whereas that of the left inferior frontal gyrus was decreased in perimenopausal women. Moreover, the GMV value of the left gyrus rectus was decreased, and this may be a potential cause of changing emotions in perimenopausal women.…”
Section: Discussionsupporting
confidence: 49%
“… 18 , 19 The regulation of cognitive function by estrogen is usually associated with the activation of the prefrontal cortex, which regulates the activation of cognition-related regions in the cerebral cortex. 20 , 21 In this study, we found that the ALFF value of the left gyrus rectus was increased, whereas that of the left inferior frontal gyrus was decreased in perimenopausal women. Moreover, the GMV value of the left gyrus rectus was decreased, and this may be a potential cause of changing emotions in perimenopausal women.…”
Section: Discussionsupporting
confidence: 49%
“…It is now accepted that ovariectomized (OVX) adult rodents share common features with aged animals regarding brain function, including changes in mitochondrial function, synaptic plasticity, behavior and cognition (Zárate et al, 2017b). To characterize our animal model of surgical menopause in adult Wistar rats at the behavioral level, we assessed parameters of spatial working memory, anxiety and depression, which are known to be modulated by ovarian hormones (Diz-Chaves et al, 2012; Kiss et al, 2012; Cao et al, 2013; Rodríguez-Landa et al, 2017; Hampson, 2018; da Silva Moreira et al, 2016). Twelve-week ovarian hormone-deprived rats showed lower spontaneous alternation behavior in the Y-maze, indicating impaired spatial working memory (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive reports suggest the particular involvement of estrogen on the working memory [ 86 , 87 ]. In an ovariectomy performed on rodents, both spatial and nonspatial working memory deficits were observed, and the estradiol treatment also rescued those deficits [ 88 ].…”
Section: Estrogen Receptor Signalingmentioning
confidence: 99%